Scenario-based urban regeneration through a contextual approach: insights from the Antalya Haşim İşcan neighbourhood - Erturk, Serpil Fatma; Kerestecioglu, Server Funda (TAYLOR & FRANCIS LTD, 2026)
This study underscores the importance of integrating the enhancement of existing buildings and urban fabrics with broader urban sustainability goals. This research introduces the Context-Based Integrated Regeneration Model (CBIRM), a holistic, multi-scalar, and scenario-driven framework that develops enhancement strategies by linking spatial relationships between building and urban scales in spatial and social contexts. It is tailored to the city's unique structural, social, and cultural dynamics, ensuring alignment with higher-level strategic sustainability goals. The analytical framework focuses on settlement patterns, street layouts, block structures, building typologies, land use, accessibility, and place identity. Enhancement scenarios tailored to distinct character areas are developed, and their alignment with criteria derived from seven urban sustainability indices is evaluated through expert interviews and a structured survey. The findings indicate that strategies prioritizing spatial quality, social engagement, and structural adaptability are more effective than those focused only on technical solutions, suggesting that meaningful sustainability outcomes emerge from efforts grounded in the local urban context. This study develops a conceptual and empirical framework that demonstrates the potential of context-based approaches in linking building-city scale interventions with urban sustainability goals. The findings contribute to ongoing discussions on heritage conservation, the transformation of urban centers, and sustainable urban development.
Keywords: Constructed contextual theory; built environment; urban regeneration; contextual sustainability; urban sustainability; SUSTAINABILITY; Architecture; Construction & Building Technology